2018
DOI: 10.14488/bjopm.2018.v15.n4.a15
|View full text |Cite
|
Sign up to set email alerts
|

Computational simulation applied in choosing the best solution in a product development using design for manufacturing and assembly approach

Abstract: Highlights: The product development methodology aims to assist the planning and design of the product throughout its life cycle. Using selection criteria it is possible to choose a solution will be followed until the end of the development process and this process is known as optimization of product solutions. Design for Manufacturing and Assembly (DFMA) is an approach that allows selecting a product solution with better manufacturing and assembly performance. Computational modeling allows representing systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…By comparing the results with the existing products, it was found that the new products designed using the DFM approach had an impressive performance in terms of reduced CO 2 emissions, improved resource efficiency, production assembly time and product complexity. However, like Pinheiro et al [44], this study fails to consider product family design and fails to include product production costs while considering sustainability.…”
Section: Customer Perceived Valuementioning
confidence: 95%
See 3 more Smart Citations
“…By comparing the results with the existing products, it was found that the new products designed using the DFM approach had an impressive performance in terms of reduced CO 2 emissions, improved resource efficiency, production assembly time and product complexity. However, like Pinheiro et al [44], this study fails to consider product family design and fails to include product production costs while considering sustainability.…”
Section: Customer Perceived Valuementioning
confidence: 95%
“…Therefore, the author concludes that applying DFMA methodologies in the early phase of product design can reduce parts count so as to reduce the total costs. Pinheiro et al [44] take the pet warm raincoat production as an example and use the DFM as a framework to select the optimal production solution according to different scenarios using the discrete-event system simulation model. The simulation results show that the selected production solution has an outstanding performance in production time, resource utilisation, and production cost through computer simulation and considering the DFM approach.…”
Section: Customer Perceived Valuementioning
confidence: 99%
See 2 more Smart Citations
“…BIM's ability to model and create simulations is highly beneficial in decision making [64]. Modelling and simulation would enable designers and stakeholders to evaluate the methods used in construction activities by representing the actual construction and simulating the cause and effect of a system before the actual construction is undertaken [4,65]. This could lead to producing a digital twin for a project.…”
Section: The Enabling Factors For Dfma Application In the Constructio...mentioning
confidence: 99%